EXPLORING THE MULTIPLICITY OF COLONIALITY: A FOCUS ON THE AGENCY OF INTERNET PROSUMERS IN THE GLOBAL SOUTH IN THE COLONIALITY PROJECT. - Ooko, Gloria Anyango (AoIR Selected Papers of Internet Research, 2023)
This paper provides a critique to the limitation of decoloniality discourses which take a unilateral approach in which hegemony is seen as originating from the Global North and resistance as located in the Global South. The article therefore aims to “voice” out the silent ways in which internet users in the Global South could be enhancing coloniality and thwarting attempts at decolonisation. Consequently, it seeks to contribute to the theorization of coloniality by privileging the concept of hybridity not as a logic of resistance but as a hegemonic site in which power inequalities and othering is perpetuated. To support the arguments made in this article, two political WhatsApp communities (East Asembo Development Forum and Kabula Forward) in Kenya imagined around the rural physical communities from which members originate, were purposively selected. The goal of both communities is to hold their political leaders accountable and agitate for development. Adapting netnography as a method which allows for researcher immersion in online spaces, data was collected through background listening, interviews and Focus Group Discussions. Data was analysed through a Discursive Material Analysis in which both the WhatsApp technology affordances/constraints and human actors’ actions, were read as text. Findings show that despite the plurality (hybridity) of the composition of the WhatsApp communities, participation is defined through hegemonic capitalism discourse, through which political participation is metaphorically substituted by materialism.